Wild canids and felids differ in their reliance on reused travel routeways - William F. Fagan; Ananke G. Krishnan; Christen H. Fleming; Elizabeth Ferreira; Stephanie Chia; Anshuman Swain; Briana Abrahms; Chloe Bracis; Eliezer Gurarie; Thomas Mueller; Michael J. Noonan; Luiz Gustavo R. Oliveira-Santos; et al. (Proceedings of the National Academy of Sciences, 2025)
Diverse factors, including environmental features and cognitive processes, can drive animals’ movements and space use, with far-reaching implications. For example, repeated use of individual-level travel routeways (directionally constrained but imperfectly aligned routes), which results in spatial concentration of activity, can shape encounter-based processes including predation, mate finding, and disease transmission. However, how much variation in routeway usage exists across species remains unknown. By analyzing GPS movement tracks for 1,239 range-resident mammalian carnivores—representing 16 canid and 18 felid species from six continents—we found strong evidence of a clade-level difference in species’ reliance on repeatedly used travel routeways. Across the global dataset, tracked canids had a 15% (±7 CI) greater density of routeways within their home ranges than did felids, rising to 33% (±16 CI) greater in landscapes shared with tracked felids. Moreover, comparisons within species across landscapes revealed broadly similar home range routeway densities despite habitat differences. On average, canids also reused their travel routeways more intensively than did felids, with hunting strategies and spatial contexts also contributing to the intensity of routeway usage. Collectively, our results suggest that key aspects of carnivore routeway-usage have an evolutionary component. Striking interspecific and clade-level differences in carnivores’ reliance on reused travel routeways within home ranges identify important ways in which the movement patterns of real-world predators depart from classical assumptions of predator-prey theory. Because such departures can drive key aspects of human-wildlife interactions and other encounter-based processes, continued investigations of the relationships between movement mechanisms and space use are critical.